Problems of Subject Raising Constructions among Yoruba ESL Learners - Raheem, Razaq Akolawole (Yoruba studies review, 2022)
Raising is an upward movement that concerns structures whose derivation involves copy, merger, and deletion and movement operations in the Minimalist Program. The proficiency of Yorùbá ESL learners and speakers of English is hindered as a result of interference from the mother tongue and divergence in raising constructions. Thus, this study examines subject-raising constructions in English and Yorùbá to explicate the root cause of the problem and the extent to which Yorùbá learners of English could be affected. Chomsky’s copy-theory of movement is adopted as the theoretical framework. Data for both languages are drawn from syntax literature. The Yorùbá data are supported with introspection. Different types of subject raising such as subject-to-subject, object-to-subject raising and raising of the clause to the subject position are carefully studied. This study discovers that subject raising in English is different from what is permitted in Yorùbá. A raised element in Yorùbá often leaves behind a presumptive pronoun for convergence. While raising is permitted in non-finite structure in English, Yorùbá allows raising in a finite clause. Therefore, raising structures especially subject raising, are not easy for Yorùbá learners of English due to language variations. Thus, learners are forced to avoid the structure or misapply their LI knowledge on similar construction in the English language. It is concluded that teachers of English should be aware of these areas of difficulties for effective teaching and learning processes.